2013
DOI: 10.1517/13543784.2013.783565
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin DPI in non-cystic fibrosis bronchiectasis: a Phase II randomized study

Abstract: On short-term basis C-DPI is able to reduce the sputum bacterial load in such patients but long-term studies are also needed to better characterize the clinical efficacy of this compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…After screening the titles and abstracts, we retrieved 17 potentially relevant full-text articles for further evaluation. Nine articles [6,[12][13][14][15][16][17][18][19] were excluded for reasons shown in figure 1. The findings of one trial were reported by BARKER et al [9] in 2000 and by COUCH [20] in 2001, so this trial was labelled as BARKER 2000 and COUCH 2001.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…After screening the titles and abstracts, we retrieved 17 potentially relevant full-text articles for further evaluation. Nine articles [6,[12][13][14][15][16][17][18][19] were excluded for reasons shown in figure 1. The findings of one trial were reported by BARKER et al [9] in 2000 and by COUCH [20] in 2001, so this trial was labelled as BARKER 2000 and COUCH 2001.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…The most consistent finding has been a reduction of bacterial density, usually P. aeruginosa with eradication described in 30–35% (and eradication up to 93% of other Gram‐negative bacteria) . Reduction in myeloperoxidase, free elastase and CRP has been reported but not consistently and such reductions were not related to clinical improvements.…”
Section: Long‐term Treatments Of Bronchiectasismentioning
confidence: 97%
“…82 The SGRQ improved in four of the six studies 18,81,82,84 and the Quality of Life-Bronchiectasis (QOLB) questionnaire 105 improved in one aztreonam study. 18,81 The most consistent finding has been a reduction of bacterial density, usually P. aeruginosa 20,[82][83][84]104 with eradication described in 30-35% (and eradication up to 93% of other Gram-negative bacteria). 18,80,82,84 Reduction in myeloperoxidase, free elastase 82 and CRP 84,104 has been reported but not consistently 19 and such reductions were not related to clinical improvements.…”
Section: Should Long-term or Rotational Antibiotics Be Used?mentioning
confidence: 97%
See 1 more Smart Citation
“…Systemic exposure was slightly higher with the 48.75 mg dose; however, the peak sputum concentrations and area under the concentration-time curve (AUC) values were similar with the two doses, which led the authors to recommend advancing the lower dose into later-phase trials. The same DPI formulation of ciprofloxacin is also being evaluated in patients with noncystic fibrosis bronchiectasis [80,81]. Limited pharmacokinetic data have been published; however, preliminary efficacy studies have demonstrated that a dose of 32.5 mg twice daily for 28 days was well tolerated and reduced the sputum bacterial load in comparison with placebo-treated subjects [81].…”
Section: Ciprofloxacinmentioning
confidence: 99%